Research Instrument: Instrument Development and Instrument Calibration - Alip Nuryanto; Naf’an Tatihoran; Rizal Firdaus (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2025)
The development and calibration of research instruments are crucial components in ensuring the accuracy and reliability of data collection in educational and social sciences. This study addresses the issues surrounding the creation and refinement of research instruments, emphasizing the importance of instrument validity and reliability. The purpose of this discussion is to explore the process of developing effective research instruments and the calibration methods required to improve their precision. This study uses a qualitative research approach, involving the collection of data through interviews, expert consultations, and a review of existing literature. Data analysis was performed using thematic analysis to identify key trends in instrument development and calibration practices. The findings highlight that developing an effective research instrument requires careful consideration of the research objectives, context, and target population. Calibration of instruments is essential to ensure that they measure accurately and consistently across different settings. The impact of this study is significant, as it provides insights into best practices for developing and calibrating research tools that can be applied across various disciplines. In conclusion, the research emphasizes the importance of continuous testing and refinement of instruments to enhance the validity and reliability of research findings.